Exposure to tacrolimus trough levels below 6 ng/ml during the first year is associated with inferior kidney graft survival. Issue 3 (20th December 2022) - Agur, Timna; Rahamimov, Ruth; Zingerman, Boris; Bielopolski, Dana; Lichtenberg, Shelly; Nesher, Eviatar; Rozen‐Zvi, Benaya
Abstract: Background: Accumulating data indicate that sub‐therapeutic levels of tacrolimus are associated with long‐term kidney graft loss. However, elevated doses increase the risk of infection and drug toxicity, which also threaten graft and patient longevity. We sought to determine the minimal tacrolimus level required to maintain graft survival. Methods: We conducted a single‐center historical cohort study. The first‐year post‐transplant exposure time was calculated for each of the five tacrolimus trough level intervals. This measure was adjusted to the exposure time below a given interval level, allowing us to define the threshold for the optimal tacrolimus level as the upper limit of the interval. We then determined the association between the adjusted exposure time at each tacrolimus level interval and our primary outcome, death‐censored graft loss. Results: One thousand four hundred and seventeen patients with a median follow‐up of 5.3 years were included in the final cohort. The tacrolimus level interval of 5–6 ng/ml was the highest interval, which demonstrated a statistically significant association between adjusted exposure time and increased risk of graft loss (HR 1.58, per log days, p  = .002). Cumulative exposure time above 14 days with a tacrolimus level below 6 ng/ml was associated with an increased rate of graft loss in most studied subgroups, except for recipients with pre transplant diabetes. Conclusions: Maintaining tacrolimus levels above 6 ng/ml during the first‐year post‐transplant might improve kidney graft survival.